Caracterización morfológica e identificación de zonas potenciales de conservación de guarumo (Cecropia Hololeuca), en los siete transectos del proyecto banco de germoplasma - Álvarez Barahona, Patricia Katheryn (2016)
This research: morphological characterization and identification potential in guarumo’s conservation areas (Cecropiahololeuca) in seven transects Gernoplasma Bank Project was conducted in the parishes of La Mana and la Esperanza with the objective to characterize and identify the potential conservation areas as a strategy to preserve native ecosystems. Morphologic determination the guarumo’s species (Cecropiahololeuca), identified the 21 pickings samples in the 7 transects the Gernoplasma bank project, which to detail them was divided into quantitative and qualitative, it was characterized in based in theoretical foundations of the species for detailing....